Characterization of multiple drug-resistants pathogens isolated from clinical and environmental samples from nephrology unit of Hospital Serdang - Suntharamurthy, Seenu (2013)
Nosocomial infections are generally hospital acquired diseases, and is posing a serious threat to mankind due to treatment failures. It is an infection occurring in a patient during the process of care in a hospital or other health-care facility that was not manifest or incubating at the time of admission. Nosocomial pathogens are often multiple drugs resistant and their emergence leads to difficulty in treatment of diseases. The common nosocomial pathogens are Methicillin-resistant Staphylococcus aureus (MRSA), Extended-spectrum beta-Iactamases (ESBL) Escherichia coli and Klebsiella pneumoniae, multi-drug resistant Pseudomonas aeruginosa and multi-drug resistant Acinetobacter baumannii. Nosocomial pathogens are continually evolving in resistance against antibiotics despite proper management control. The main aim of this study is to characterize multi drug resistant (MDR) pathogens isolated from clinical and non-clinical sources isolated from the Nephrology unit in Hospital Serdang. Among the objectives were to determine phenotypic and genotypic characteristics of the common nosocomial pathogens isolated, to determine the antimicrobial susceptibility pattern and resistant genes, and fmally to determine the clonality of the MDR pathogens. Nasal and hand swabs were obtained from the healthcare workers, their belonging and ward environment. All swabs were screened for the common MDR pathogens using standard procedure. In order to characterize the pathogens, all MDR clinical isolates isolated from patients admitted in the Nephrology from September 2011 to May 2012 were collected. DNA extraction was performed and antibiotic resistant genes such as mecA, tem, shv, OXA-23, OXA-5i, Inti, sull, qacA, qacE and bla-IMP coding for methicillin resistance, cephalosporinases, carbapenemases, and quaternary ammonium compounds were screened using simple peR. Among the four sampling groups (nasal and hands of healthcare workers, their personal belonging and the ward environment), 43 isolates were S. aureus, 9 were P. aeruginosa, 23 were K. pneumoniae, 10 were E. coli and 16 were A. baumannii. Antimicrobial Susceptibility Testing (AST) performed on all isolates to screen for the MDR strains showed the following results: S. aureus showed high resistance to penicillin (51.16%), followed by cefoxitin and erythromycin (16.28%); P. aeruginosa showed high resistance to chloramphenicol (63.64%), followed by ceftazidime (36.36%); A. baumannii showed high resistance to ceftazidime and chloramphenicol (43.75% each), followed by ampicillin-sulbactam (31.25%); E. coli showed high resistance to ampicillin (50.0%) and co-trimoxazole (50.0%), while augment in, aztreonam and ceftriaxone showed 40% resistance; K. pneumoniae showed 100% resistance to ampicillin and augmentin. All resistant isolates were screened for antibiotic resistant genes. Among the clinical isolates, one MRSA isolate carried the mecA and smr gene. The genes tern and shv were observed in ESBL E. coli. One isolate showed positive signal for the shv gene and negative for tern. Two isolates showed positive signal for the tern gene but negative for shv. Although resistance was observed for P. aeruginosa in AST, no resistant genes were detected. Only one isolate of A. baumannii showed positive signal for tern, bla-IMP, OXA-23 and OXA-51. All genes were confirmed by sequence analysis. PFGE was performed to trace any transmission of MDR pathogens from healthcare workers or the ward environment to the patients. All MDR pathogen isolated from clinical and non-clinical samples were fingerprinted by PFGE method (five isolates of P. aeruginosa, six isolates of S. aureus, and three isolates of ESBL E. coli). The dendrogram generated showed a vast diversity among the strains. No close relatedness was observed between the isolates from the HeWs, their belongings, and the environment with the clinical isolates. Further study need to be conducted including more wards from the hospital to understand the epidemiology of nosocomial pathogens in the hospital.